Socio-philosophical analysis of trends in the development of urban culture - Manassova, M.M.; Karipbaev, B.I. (KU Publ., 2022)
This article discusses the nature and appearance of cities, manifestations of the phenomenon of urban culture. First, it analyses the features of cities in the various stages of the development of society. Second, it assesses the changing role of the modern city. Third, urban development and the changing role of capital in modern Kazakhstan. The authors examines the city as part of a variety of socio-economic systems. Formulated theoretical and methodological approaches used to study the major trends and issues of socio-economic dynamics of cultural cities. The authors analyzes the current state of urban culture and cultural values of cities in the world development. In conclusion, the authors develop their own understanding of the role of Nur-Sultan in the cultural and civilizational development of Kazakhstan.
Қала мәдениетінің даму тенденцияларын әлеуметтік-философиялық талдау
Социально-философский анализ тенденций развития городской культуры
Keywords: function of cities; urban culture; civilization; Kazakhstan; capital; Nur-Sultan; Astana; postmodern city; postindustrial city; urbanization